Investigating the Impact of Leverage and Managerial Skills on Firm Performance - Syed Amad Nadeem (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
The goal of this research is to look into the impact of leverage and managerial skills on shareholder returns. In this study, the proportion of debt in the firm’s total capital structure is of particular importance. Total debt and long-term debt are used to calculate leverage. Each company’s CEO’s managerial skills are evaluated based on his or her education and experience. The return on equity is used to calculate the value of a stockholder’s investment. Different firms use different capital structures and it is a difficult task for a manager to decide what capital structure minimizes risk and cost while maximizing shareholder wealth and firm value. In this study, I used panel data analysis on a sample of 25 companies from 2009 to 2014. The companies were chosen from Pakistan’s agricultural sector. According to the findings of panel data analysis, there is a significant and positive relationship between a firm’s total debt and return on equity. Similarly, the findings show a significant and negative relationship between a firm’s total debt and return on equity. Return on equity is found to have a significant and positive relationship with the CEO’s education level and experience. Long-term debt, on the other hand, has a negative but significant relationship with return on equity. According to the findings, as a company’s debt grows, so does its return to shareholders. Similarly, increasing only long-term debt reduces stockholder returns.